Solving the boar taint problem : development of an immunoassay for the detection of skatole - Puolasmaa, Pekka (My University, 2021)
Boar taint is the undesirable smell sometimes emitted when cooking pork from entire male pigs, aka boars. It is caused by a male hormone androstenone and a bacterial metabolite of tryptophan known as skatole. Male piglets are typically castrated to prevent the formation of boar taint and reduce aggressive behavior. The EU has set goals to abolish the surgical castration of piglets to increase the well-being of farm animals. Boar taint is generally not accepted by consumers, and thus there is a need for a method to rapidly detect boar taint at the butchery. As of 2017, no commercial rapid screening test existed, and the current detection methods required skilled personnel and expensive equipment. An antibody against skatole was discovered using phage display in the department of biotechnology in 2015 by Leivo et al. The aim of this thesis was to screen improved antibodies and establish a homogenous immunoassay utilizing up-converting nanoparticles (UCNP’s) to detect skatole from whole blood of boars. After screening, the antibodies with the highest affinities were produced in shake flask cultivations. The his-tagged antibodies were purified using immobilized metal affinity chromatography (IMAC) and then conjugated with UCNP’s. During the study it was noticed that the quality of antibodies was inconsistent, and they tended to lose activity during storage. Multiple attempts were made to eliminate the problem, including chromatography optimization, additional purification with size exclusion chromatography, and a new production strain modified to reduce IMAC contaminants. UCNP-antibody conjugations were successful, and they were confirmed to specifically bind to skatole. However, there was not enough time to start the assay development due to the problems with the antibodies.
Keywords: skatole, boar taint, scFv, IMAC, immunoassay, UCNP